An Experimenter's Influence on Motor Enhancements: The Effects of Letter Congruency and Sensory Switch-Costs on Multisensory Integration - Barutchu, Ayla; Spence, Charles (Frontiers in Psychology, 2020)
Multisensory integration can alter information processing, and previous research has shown that such processes are modulated by sensory switch costs and prior experience (e.g., semantic or letter congruence). Here we report an incidental finding demonstrating, for the first time, the interplay between these processes and experimental factors, specifically the presence (vs. absence) of the experimenter in the testing room. Experiment 1 demonstrates that multisensory motor facilitation in response to audiovisual stimuli (circle and tone with no prior learnt associations) is higher in those trials in which the sensory modality switches than when it repeats. Those participants who completed the study while alone exhibited increased RT variability. Experiment 2 replicated these findings using the letters ‘b’ and ‘d’ presented as unisensory stimuli or congruent and incongruent multisensory stimuli (i.e., grapheme-phoneme pairs). Multisensory enhancements were inflated following a sensory switch; that is, congruent and incongruent multisensory stimuli resulted in significant gains following a sensory switch in the monitored condition. However, when the participants were left alone, multisensory enhancements were only observed for repeating incongruent multisensory stimuli. These incidental findings, therefore, suggest that the effects of letter congruence and sensory switching on multisensory integration are partly modulated by the presence of an experimenter.